1995
DOI: 10.1021/j100031a029
|View full text |Cite
|
Sign up to set email alerts
|

Xenon NMR Study of a Nematic Liquid Crystal Confined to Cylindrical Submicron Cavities

Abstract: NMR studies of xenon gas dissolved in the liquid crystal ZLI 1132 confined to submicron cylindrical cavities are reported. Spectra taken as a function of temperature yield a clear indication of the nematic to isotropic phase transition of the confined liquid crystals. In the nematic phase at 21 "C, the resonance line of dissolved 129Xe exhibits a chemical shift anisotropy of 15 ppm due to a random distribution of director axes in the plane perpendicular to the long axis of the cylinder. The anisotropy and temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…Zeolite ZSM‐5 was studied with MAS 13 C NMR spectroscopy, and chemical exchange was seen for both slow rotation and for exchange from straight channels in the zeolite to zig‐zag channels. Pines et al . elegantly used 129 Xe‐ 29 Xe EXSY to study a nematic liquid crystal.…”
Section: Non‐covalent Molecular Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zeolite ZSM‐5 was studied with MAS 13 C NMR spectroscopy, and chemical exchange was seen for both slow rotation and for exchange from straight channels in the zeolite to zig‐zag channels. Pines et al . elegantly used 129 Xe‐ 29 Xe EXSY to study a nematic liquid crystal.…”
Section: Non‐covalent Molecular Recognitionmentioning
confidence: 99%
“…[141] Many solidse ngage in host-guest dynamics, and these can be studied by using solid exchange NMR spectroscopy.Z eolite ZSM-5 [142] was studied with MAS 13 CNMR spectroscopy,a nd chemicale xchange was seen for both slow rotation and fore xchange from straight channels in the zeolite to zig-zag channels. Pines et al [143] elegantly used 129 Xe- 29 Xe EXSY to study a nematicl iquid crystal.E xperiments showedc hemical exchange between the gas and the liquid crystal sites. Similar exchange in al iquid crystal is seen by Jokisaariand co-workers.…”
Section: Host-guest Pairsmentioning
confidence: 99%
“…In many studies of zeolites, [14][15][16][17][18][19][20][21][22][23][24] it has been reported that the δ(S) value is strongly correlated with the size and nature of a hole in which Xe is sorbed. For polymer systems, [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] in addition, some researches have also been reported about the relation between 129 Xe NMR chemical shift and size of hole that gives free volume or microvoids. Similarly it will be able to evaluate the size of the cavity in PMP crystal from δ(S) value.…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16] The 129 Xe NMR signal is sensitively influenced by its environment, and the induced 129 Xe NMR chemical shifts strongly correlate to the microvoid size because certain interactions with the host system disturb the Xe electron density. It has been reported by our research group that the mean microvoid size in glassy polymers can be determined based on the Xe density dependence of the 129 Xe NMR chemical shift.…”
Section: Introductionmentioning
confidence: 99%